2022
DOI: 10.1155/2022/9571217
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Intensity Light‐Responsive Anticancer Activity of Platinum(II) Complex Nanocolloids on 2D and 3D In Vitro Cancer Cell Model

Abstract: This study aimed to evaluate the therapeutic efficacy of low-intensity visible light responsive nanocolloids of a Pt-based drug using a 2D and three-dimensional (3D) in vitro cancer cell model. Biocompatible and biodegradable polymeric nanocolloids, obtained using the ultrasonication method coupled with Layer by Layer technology, were characterized in terms of size (100 ± 20 nm), physical stability, drug loading (78%), and photoactivation through spectroscopy studies. The in vitro biological effects were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…They found a stronger green fluorescence associated with curcumin in the synthesized nanoparticles in comparison to the free complex. In our previous work, 49,50 we have already demonstrated that also the fluorescence of curcumin alone decays after 1 h of incubation.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…They found a stronger green fluorescence associated with curcumin in the synthesized nanoparticles in comparison to the free complex. In our previous work, 49,50 we have already demonstrated that also the fluorescence of curcumin alone decays after 1 h of incubation.…”
Section: Resultsmentioning
confidence: 80%
“…Ultrasonication assisted layer by layer technology was employed for the preparation of nanocolloids. 49,50 Dynamic light scattering (DLS) measurements revealed that the size of nanocolloids was uniform, and the average diameter was 190 ± 10.32 nm (Fig. 1a).…”
Section: Physical Chemical Characterization Of Nanocolloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic balance of metabolic processes that underlie the restoration or, conversely, the degradation of the cell's vital functions is disturbed [41,42]. Apoptosis due to ROS-induced ROS production can be a predictable phenomenon because it is an evolutionarily programmed scenario if metabolic changes become incompatible with normal functioning [43,44]. The initiation of apoptosis processes may seem all the more likely when we understand that destructive changes in the cell are generated not by one but by several influencing factors: laser irradiation and doxorubicin [45,46].…”
Section: Fig 10 Mechanisms Of Pro-apoptotic Action Of Laser Irradiationmentioning
confidence: 99%